2020
DOI: 10.1021/acs.jpcc.9b11371
|View full text |Cite
|
Sign up to set email alerts
|

Zeta Potential Determination from Molecular Simulations

Abstract: ζ-Potential (ZP) is among key physical properties characterizing the behavior of nanoparticles in colloidal solutions. Despite many attempts to calculate and neatly interpret the ZP, a full understanding of various factors influencing its values has not been achieved yet, even for standard metal oxides, particularly when considering high ionic concentrations and the effect of temperature. This contribution extends our recent work [Prědota, M. et al. Langmuir 2016, 32, 10189−10198], where we suggested a direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 102 publications
2
54
1
2
Order By: Relevance
“…MD studies of solid-liquid interfaces have shown a diverse picture, with ion adsorption varying largely between studies. [25][26][27][28][29][30][31][32][33][34][35][36] For example, Lorenz et al 26 predicted charge inversion in silica nanochannels with a bare surface charge density of −144 mC/m 2 filled with 200 mmol/l CaCl 2 , while Biriukov et al 36 predicted no charge inversion under similar conditions. In fact, many MD simulation studies predict charge inversion at bulk ion concentrations much lower than inferred from experiments.…”
Section: Introductionmentioning
confidence: 99%
“…MD studies of solid-liquid interfaces have shown a diverse picture, with ion adsorption varying largely between studies. [25][26][27][28][29][30][31][32][33][34][35][36] For example, Lorenz et al 26 predicted charge inversion in silica nanochannels with a bare surface charge density of −144 mC/m 2 filled with 200 mmol/l CaCl 2 , while Biriukov et al 36 predicted no charge inversion under similar conditions. In fact, many MD simulation studies predict charge inversion at bulk ion concentrations much lower than inferred from experiments.…”
Section: Introductionmentioning
confidence: 99%
“…A direct numerical measurement of the zeta-potential for the system (110)-rutile TiO 2 surface interacting with aqueous electrolyte was obtained by electro-osmosis experiments. 33,35 In such experiments, the zeta-potential is proportional to the flow velocity, v 0 , and the applied electric field, E x , according to 50…”
Section: From the Structural Properties Of The Interface To A Macroscopic Definition Of The Interfacementioning
confidence: 99%
“…Within this idea, numerous in silico experiments in the MD framework were performed to reveal structure-property relationships for the rutile-(110) TiO 2 /water system. 8,[28][29][30][31][32][33] Although the hydroxylation of the surface was (i) explicitly considered in classical, non-reactive MD approaches for modeling charged surfaces, 8,[33][34][35] or (ii) dynamically evolving using a reactive force field to analyze electrostatic properties of the rutile-TiO 2 /water system 31 or to quantify the surface reactivity of different TiO 2 polymorphs, 36 a defect-free titania surface interacting with bulk water or aqueous electrolyte is the common assumption to both classical MD studies and the ones performed using a reactive force field. Recently, it was reported that dissociation kinetics of a water molecule was around 20 times faster on a defective rutile-(101) TiO 2 surface than on the defect-free surface.…”
Section: Introductionmentioning
confidence: 99%
“…The key role in this pumping phenomenon is played by the electrically charged solid-liquid interface, the so-called electrical double layer (EDL). The EDL, which is a composition of charged solid surface and a very tiny layer of counter-charges in an aqueous solution (around a few nanometers), was first investigated in the 19th century [12], and has been further studied in the 20th century [13][14][15] and in contemporary times [16][17][18][19][20]. Consequently, it is of utmost importance to enhance our understanding of the configuration of water and ionic species in the vicinity of an electrically charged solid surface.…”
Section: Introductionmentioning
confidence: 99%
“…Figure20. Pressure generated by employing an external electric field toward a micro-size packed silica beads.…”
mentioning
confidence: 99%